The effectiveness of thinking maps in the achievement of students of the Institute of Fine Arts Article analysis and technical criticism (Journal of the College of Basic Education, 2023)
Summary of the research :The study aimed to know the effectiveness of thinking maps in the achievement of the students of the Institute of Fine Arts in the subject of criticism and technical analysis. To achieve the goal of the research, the researchers used the one-group experimental design with a pre- and post-test for the subject of criticism and technical analysis for its suitability on a sample of fifth grade female students from the Institute of Fine Arts, the fifth grade, and the research sample consisted of (11) students as an experimental group, and to reach the results of the research, The research tool was a cognitive achievement test for the subject of criticism and technical analysis. The researchers analyzed the data into systematic images for their research using the statistical bag for social sciences (SPSS).The most important search results showed the following:1- The strategy of thinking maps has a high ability to increase the achievement of students and increase their participation in the lesson, which led to an increase in the effectiveness of students towards the lesson.2- The ability of the thinking maps strategy to provide students with cognitive information related to the subject of criticism and artistic analysis in the fifth stage, the Institute of Fine Arts, which was reflected in their ability to analyze artistic subjects and their answers to the test items prepared for this purpose.Recommendations:In light of the results and conclusions reached by the researchers, they recommend a number of recommendations, including:1. Training teachers of fine arts institutes on how to use the thinking maps strategy by the Ministry of Education and through in-service training courses.2. The need to train female and male students in the institutes of fine arts on the strategy of thinking maps to be used in the educational process.Suggestions:In order to complement and develop the current research, the researchers suggested the following:1. Conducting a study to measure achievement in acquiring social experiences using thinking maps according to the gender variable.Keywords: effectiveness - thinking maps - analysis and business criticism.